the effectiveness of the Mandarin Language Curriculum Study Materials on the Mandarin Language Skill of Students' Ability: KEEFEKTIFAN BAHAN KAJIAN KURIKULUM BAHASA MANDARIN TERHADAP KEMAMPUAN MAHASISWA BERBAHASA MANDARIN - AIGA VENTIVANI (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2020)
ABSTRACT Changes of curriculum are reasonable to continue to be better. These changes need to be known and well accepted by students as one form of achieving learning goals. One way to find out whether the curriculum is well received or not by undergraduate students of Chinese Education Study Program of Malang Learning University , is through the current level of curriculum effectiveness. This study aims to determine the effectiveness of Chinese Language Education Study Program Curriculum in Malang State University . The method used in this research is descriptive quantitative, while the instrument used in this study is to use the 汉语 水平 考试 （年级） test [Hànyǔ shuǐpíng kǎoshì (sān niánjí)]. Subjects in this study were all first-year, second-year and third-year students of Mandarin language education at State University of Malang. This study uses product moment correlation analysis using the Pearson formula. The results showed that the curriculum used was effective in improving Mandarin language skills of Chinese Language Education students at Malang State University.